Study on the Recognition and Purchase Status of Eco-Friendly Oral Hygiene Products - Su-min Jeon; Do-Seon Lim; Jae-kyeong Kim; Jae-ui Lee; Su-hyeon Lee; Seong-eun Park; Im-hee Jung (치위생과학회지, 2022)
Background: Plastic waste generates pollutants in the process of incineration or landfilling, and accumulates in water or marine organisms, causing adverse effects on the environment and the human body. Recently, various eco-friendly oral hygiene products (Eco-OHPs) such as bamboo toothbrushes and biodegradable plastic toothbrushes have been developed. Therefore, this study aimed to investigate the current level of awareness and purchasing status of eco-OHPs among adults who are interested in eco-friendly products.Methods: This study included adults aged ＞19 years who regularly visited eco-friendly shops and online sites; the online survey links were distributed during their visits to eco-friendly Internet cafés and companies. Of the 22 questions, seven assessed the participants’ general characteristics, three assessed the general oral hygiene care products used, six assessed the level of awareness of Eco-OHPs, and six assessed the purchasing status of Eco-OHPs. Frequency analysis, chi-square test, and regression analysis were performed using SPSS software. Results: Among the respondents, 108 (51.4%) were aware of Eco-OHPs, and 79 (37.6%) had experience purchasing Eco-OHPs. The most common reason for not purchasing was the lack of information about related brands or products (74, 56.5%). The most common platform used in obtaining information was the Internet (general: 31.5%, eco-friendly: 46.3%), such as Social Network Service, Internet cafes, and blogs. The experience in purchasing Eco-OHPs was affected by whether the respondents recognized the possibility of contributing to environmental preservation, availability of vendors, product safety, and the number of eco-friendly products purchased. Conclusion: In order to expand the use of Eco-OHPs, various efforts such as promotion of eco-friendly characteristics, determination of related vendors, reliable analysis of product safety, and expansion of product experience opportunities are required.